2018
DOI: 10.1530/joe-17-0258
|View full text |Cite
|
Sign up to set email alerts
|

Stem/progenitor cells in pituitary organ homeostasis and tumourigenesis

Abstract: Evidence for the presence of pituitary gland stem cells has been provided over the last decade using a combination of approaches including in vitro clonogenicity assays, flow cytometric side population analysis, immunohistochemical analysis and genetic approaches. These cells have been demonstrated to be able to self-renew and undergo multipotent differentiation to give rise to all hormonal lineages of the anterior pituitary. Furthermore, evidence exists for their contribution to regeneration of the organ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 118 publications
(176 reference statements)
0
31
0
Order By: Relevance
“…These results also suggest that PA progenitor cells do not originate early in the cytodifferentiation process but derive instead from an already partially committed cell. Undoubtedly, further elucidation of the mechanisms underlying pituitary stem cell self-renewal, differentiation and programmed death may lead to a better understanding of pituitary homeostasis, plasticity and tumorigenesis 15 .…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggest that PA progenitor cells do not originate early in the cytodifferentiation process but derive instead from an already partially committed cell. Undoubtedly, further elucidation of the mechanisms underlying pituitary stem cell self-renewal, differentiation and programmed death may lead to a better understanding of pituitary homeostasis, plasticity and tumorigenesis 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of this cell population has been observed under conditions of acute experimental stress, e.g., hormone cell type-specific cell oblation and organ loss, the extent to which this mechanism contributes to pituitary homeostasis and functional plasticity is unclear (27). Adult stem cells have also been implicated in mediating pituitary neo-plastic growth, and this pathological aspect of pituitary plasticity has been extensively covered in recent excellent reviews (28,29).…”
Section: Breakthrough Discoveries; Visualization Leading To Cell Idenmentioning
confidence: 99%
“…Su et al [37] analyzed the expression pattern of tumor stem-like cells isolated from MMQ rat prolactinoma cells and found that Bcl 2, VegfA, Pten, Jun, Fos, and Apc2 gene expressions were upregulated and the expression of Myc was downregulated in these cells. The model of cancer stem cell proposes that a small population of cells with stem-like properties initiates and maintains tumorigenesis and may be more resistant to therapy than other tumor cells [100,101]. The resistance is probably due to their often slow cycling, nonproliferative states [102] and/or the expression of ABC transporters, and high levels of aldehyde dehydrogenases [100].…”
Section: Effects Of Estradiol On Stem/progenitor Cells and Transdiffementioning
confidence: 99%